2022
DOI: 10.3390/bios12110990
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemical Detection of 4-Nitrophenol with PEDOT:PSS Modified Pt NPs-Embedded PPy-CB@ZnO Nanocomposites

Abstract: In this study, a selective 4-nitrophenol (4-NP) sensor was developed onto a glassy carbon electrode (GCE) as an electron-sensing substrate, which decorated with sol–gel, prepared Pt nanoparticles- (NPs) embedded polypyrole-carbon black (PPy-CB)/ZnO nanocomposites (NCs) using differential pulse voltammetry. Characterizations of the NCs were performed using Field Emission Scanning Electron Microscopy (FESEM), Energy-Dispersive Spectroscopy (EDS), X-ray Photoelectron Spectroscopy (XPS), Ultraviolet–visible Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…A previous study also reported similar observations. 2 The electrochemical area of the bare electrode was 0.0241cm 2 , whereas the active surface area of the modified electrode was calculated from the slope of the peak current versus V 1/2 plot and was found to be 0.1327 cm 2 . On the other hand, the sensitivity of the modified electrode was calculated to be 4.9 μA mM –1 cm –2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study also reported similar observations. 2 The electrochemical area of the bare electrode was 0.0241cm 2 , whereas the active surface area of the modified electrode was calculated from the slope of the peak current versus V 1/2 plot and was found to be 0.1327 cm 2 . On the other hand, the sensitivity of the modified electrode was calculated to be 4.9 μA mM –1 cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the modified binder-free electrodes were used for electrochemical measurements. 4-NP, a known environmental pollutant, , was used to demonstrate the sensing ability of the modified electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal nanoparticles are essential in modern analytical chemistry as nanoparticles can be used to make sensors that provide better responses from organic and inorganic substances than ordinary metal surfaces. [18][19][20][21] Gold nanoparticles, in specifically, have proven to be ideal for creating customized electrodes. [22][23][24] As a result, many organic and inorganic molecules are physically chemisorbed on gold nanoparticles without losing their catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles are essential in modern analytical chemistry as nanoparticles can be used to make sensors that provide better responses from organic and inorganic substances than ordinary metal surfaces [18–21] . Gold nanoparticles, in specifically, have proven to be ideal for creating customized electrodes [22–24] .…”
Section: Introductionmentioning
confidence: 99%